Indigenous Knowledge and the Convention on Biological Diversity - Quiggin, Robynne (The Australian Journal of Indigenous Education, 2008)
Abstract Australia is rich in biological diversity and Indigenous Australians hold substantial knowledge about how to care for and utilise a diverse range of plants and other biological elements which occur here. Australia has a specific set of legal and policy obligations arising from its ratification of the Convention on Biological Diversity in 1993. This paper looks at some of the ethical, strategic, and practical issues for Indigenous peoples.